1997
DOI: 10.1080/10934529709376585
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metal ions from aqueous solution by modified barks

Abstract: The bioconcentration of fenitrothion in the brain of the european eel (Anguilla anguilla) and its posterior elimination have been studied. Animals were exposed to a sublethal concentration of fenitrothion (0.04 mg/L) for 96 hours in a flow-through test system. After this pesticide exposure, animals were transferred to clean water for 72 hours more. Bioconcentration and elimination processes of fenitrothion were studied in blood and brain. This insecticide showed a strong tendency to bioconcentrate into selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 8 publications
1
35
0
1
Order By: Relevance
“…One of such methods is the use of adsorption. Interest has recently risen in the investigation of some unconventional methods and low cost materials for scavenging heavy metal ions from industrial waste waters [4]. In general, an adsorbent can be assumed as "low cost" if it requires little processing, is abundant in nature, or is a by-product or waste material from the industry [2].…”
Section: Introductionmentioning
confidence: 99%
“…One of such methods is the use of adsorption. Interest has recently risen in the investigation of some unconventional methods and low cost materials for scavenging heavy metal ions from industrial waste waters [4]. In general, an adsorbent can be assumed as "low cost" if it requires little processing, is abundant in nature, or is a by-product or waste material from the industry [2].…”
Section: Introductionmentioning
confidence: 99%
“…When there is only one metal available, the adsorption is non-competitive, but in treatments of industrial effluents, there are many metals available for the adsorption that may suppress each other (competitive adsorption) (Gloaguen and Morvan 1997). In contrast, Hanzlik et al (2004) reported that copper and silver were adsorbed better when both existed in solution and total metal uptake was higher than in single metal ion solutions.…”
Section: Metalmentioning
confidence: 93%
“…Extractives have advantages in heavy metal treatments: Some extractives such as flavonoids (particularly the B ring) can complex with metals in water (Vazquez et al 2002), while tannins and pectins are considered as active ion-exchange compounds with their carboxylic and phenolic groups providing active sites for metal binding (Gloaguen and Morvan 1997). Netzahuatl-Muñoz et al (2012) reported the involvement of phenolic groups of lignin and tannins present in Cupressus lusitanica bark in the Cr(III) adsorption.…”
Section: Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability has been attributed to bark pectin and tannin, and more precisely to their respective carboxylic and phenolic groups which can bind metallic cations (Aoyama et al, 1993;Kumar and Dara, 1980). The ability of barks to remove heavy metal ions from polluted solutions (Al-Asheh et al, 1998;Gaballah et al, 1997;Gloaguen et al, 1997;Seki et al, 1997;Aoyama et al, 1993;Deshkar et al, 1990;Kumar et al, 1980;Randall et al, 1974) and the impact of various operating factors on this phenomenon (Deshkar et al, 1990) are well documented. In one of our precedent papers, these interactions were modeled using a Langmuir isotherm (Martin-Dupont et al, 2002) and adsorbent performances were improved using chemical modification by attachment of anionic functions (Martin-Dupont et al, 2004).…”
Section: Introductionmentioning
confidence: 99%